KEANEKARAGAMAN IKAN (PISCES) DI DANAU SIPOGAS KABUPATEN ROKAN HULU PROVINSI RIAU - FAUZIAH, PUJI; ANTHONIUS PURNAMA, ARIEF; YOLANDA, ROFIZA; KARNO, RIA (Jurnal Biologi Udayana, 2017)
This study has been conducted from May to July 2016 to inventory the species of fish from Sipogas lake, Rokan Hulu District, Riau Province. Result showed a total of 353 individuals of fish belonging to 3 order, 7 families, 13 genera and 14 species were recorded in this study, by using survey method at 4 stations, namely Anabas testudineus, Barbodes gonionotus, Belontia hasselti, Channa striata, Cyclocheilichthys apogon, Hampala macrolepidota, Helostoma temminckii, Kryptopterus limpok, Ompok eugeneiatus, Osteochilus hasseltii, Osteochilus mycrocephalus, Pristolepis grooti, Puntius lateristriga and Rasbora sp. Cyprinidae was the predominant fish in this study.